Examining the determinants of teachers work motivation levels in teaching at public secondary schools in Melo koza Woreda, South Nations Nationalities and Peoples Regional State, Ethiopia - Milkiyas Asso Goshu (Western European Studies, 2023)
This study was aimed to examine the teachers’ work motivation level and its critical determinants in public secondary schools. The study was carried out using a convergent parallel mixed methods design.75 secondary school teachers participated in this study. Quantitative data were collected with five point Likert scale survey questionnaires, while qualitative data were collected through a semi-structured interview with five participants. The quantitative and qualitative findings indicated that the work motivation levels of the teachers varied depending on the variables of age, gender, education level, and professional experience. Furthermore, both quantitative and qualitative findings indicated that the work environment, reward system, and work itself all played a role in determining secondary school teachers' work motivation. School principals and woreda education offices are recommended to create a safe school environment by fulfilling facilities, designing and implementing teacher reward systems, and providing a variety of training opportunities in order to make the teaching and learning process more attractive and thereby to develop teachers' interest and motivation in their profession.
Keywords: Work motivation; reward system; work environment